BETWEEN THE COLONIAL AND THE NATIONAL MODERN: GENDER DYNAMICS IN EARLY CINEMA IN KERALAM - MEENA T. PILLAI
Keralam, with its erstwhile tradition of matrilineal forms of kinship pattern, has evolved into one of the most advanced states of India in terms of social development indicators. Yet in 1933, its unique form of matrilineal kinship became the first kinship system in the world to be legally abolished. In 1928, the first Malayalam silent movie Vigathakumaran was produced. Since then to the first talkies Balan (1938) and Jnanambika (1940) Malayalam cinema shows a curious fascination with the erasure of the mother and the trope of the step-mother. This paper seeks to study the emergent discourse of cinema in Keralam in the nineteen thirties and forties and explicate how it has sought in varying degrees, to consolidate and reinforce the ‘patriocal’ ideologies of a society that was continually struggling to efface a matrilineal past by pegging down with a vigour, infused by colonial modernity, the contours of a normative, ‘native’ femininity.